Dealing with people you can't stand : how to bring out the best in people at their worst - Brinkman, Rick; Kirschner, Rick (McGraw-Hill, 2002)
Focuses on the ten most unwanted types of difficult people in work situations--including the whiner, the sniper, and the know-it-all--and provides strategies for dealing with each type